(untitled) - Salzman, Philip Carl (Upper Saddle River, N.J., 2008)
12 parts: Introduction to thiking anthropoligically; what anthropologists look for: patterns; thinking Holistically; thinking ; Includes bibliographical references and index
Keywords: Anthropology -- Philosophy -- Methodology; Nhân chủng học -- Triết học -- Phương pháp luận